Auctioning monopoly franchises: Award criteria and service launch requirements - Michele Moretto; Cesare Dosi (Fondazione Eni Enrico Mattei (FEEM), 2009)
We study the competition to acquire the exclusive right to operate an infrastructure service, by comparing two different specifications for the financial proposals - lowest price to consumers vs highest concession fee, and two alternative contractual arrangements: a contract which imposes the obligation to immediately undertake the investment required to operate the concessioned service and a contract which simply assigns to the winning bidder the right to supply the market at a date of her choosing. By comparing the returns of these alternative award criteria and concessioning conditions, we show that concessioning without imposing rollout time limits may or may not provide a higher expected social value, depending on the bidding rule used to allocate the contract. In turn, the relative advantages of each award criterion are affected by the concessioning conditions.
Keywords: L51; D44; D92; 330; Concessions; Auctions; Award criteria; Service Rollout Time limits